Characterization of Groups with a Layer-Finite Periodic Part - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We prove a theorem that characterizes groups with a layer-finite periodic part in the class of the Shunkov groups with solvable finite subgroups.